Structural organization of pregenomic RNA and the carboxy-terminal domain of the capsid protein of hepatitis B virus. - Joseph C-Y Wang (Public Library of Science (PLoS), 2012)
The Hepatitis B Virus (HBV) double-stranded DNA genome is reverse transcribed from its RNA pregenome (pgRNA) within the virus core (or capsid). Phosphorylation of the arginine-rich carboxy-terminal domain (CTD) of the HBV capsid protein (Cp183) is essential for pgRNA encapsidation and reverse transcription. However, the structure of the CTD remains poorly defined. Here we report sub-nanometer resolution cryo-EM structures of in vitro assembled empty and pgRNA-filled Cp183 capsids in unphosphorylated and phosphorylation-mimic states. In empty capsids, we found unexpected evidence of surface accessible CTD density partially occluding pores in the capsid surface. We also observed that CTD organization changed substantively as a function of phosphorylation. In RNA-filled capsids, unphosphorylated CTDs favored thick ropes of RNA, while the phosphorylation-mimic favored a mesh of thin, high-density strands suggestive of single stranded RNA. These results demonstrate that the CTD can regulate nucleic acid structure, supporting the hypothesis that the HBV capsid has a functional role as a nucleic acid chaperone.